2020
DOI: 10.1007/s10896-020-00141-9
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for and Experiences of Sexual Assault Nondisclosure in a Diverse Community Sample

Abstract: Purpose-After a sexual assault (SA), victims often disclose their SA to an informal support provider (SP) to receive social support; however, many survivors do not disclose or wait months or years to tell anyone. While research exists on disclosure, social reactions of informal SPs to disclosure, and how those reactions affect the victim both positively and negatively, little research exists on reasons for and impact of adult SA survivors' nondisclosure to informal social network members.Method-This qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 40 publications
(44 reference statements)
0
33
0
Order By: Relevance
“…Moreover, the ability to choose the medium by which they made their public disclosure offered them the uniquely beneficial ability to tailor the audience and content of their disclosure—and to deal with the negative social reactions to it—through the tools offered by the online platform. This feature of selective disclosure (Ullman et al, 2020) was perceived by the participants as endowing them with the ability to promote their recovery by meeting their needs of control, safety, and autonomy, which were all the more important given the helplessness they had experienced during the sexual assault (Andalibi et al, 2016; O’Neill, 2018). However, this perceived safety-through-selective-audience may be illusory, as the individual may not be fully cognizant of the risks involved, and may find herself making disclosure to the wrong readership, rather than to the specific one that she had intended (Marwick & Boyd, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the ability to choose the medium by which they made their public disclosure offered them the uniquely beneficial ability to tailor the audience and content of their disclosure—and to deal with the negative social reactions to it—through the tools offered by the online platform. This feature of selective disclosure (Ullman et al, 2020) was perceived by the participants as endowing them with the ability to promote their recovery by meeting their needs of control, safety, and autonomy, which were all the more important given the helplessness they had experienced during the sexual assault (Andalibi et al, 2016; O’Neill, 2018). However, this perceived safety-through-selective-audience may be illusory, as the individual may not be fully cognizant of the risks involved, and may find herself making disclosure to the wrong readership, rather than to the specific one that she had intended (Marwick & Boyd, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Feelings of shame and guilt become an inevitable component of the victims’ perceptions of themselves, making it difficult for them to formally or informally disclose the assault they have experienced, discouraging them from getting professional help, and hindering recovery (Campbell, Adams, Wasco, Ahrens, & Sefl, 2009; Kennedy & Prock, 2018). Other barriers to disclosure, such as fear of negative reactions, family and social expectations, and the circumstances of the assault (e.g., the survivors’ involvement with substance use) may lead to nondisclosure or selective disclosure (Ullman, O’Callaghan, Shepp, & Harris, 2020). However, nondisclosure or selective disclosure could actually benefit survivors, by enabling them to avoid harmful reactions and revictimization by responders who target previously victimized women, whom they perceive as more vulnerable (Ullman et al, 2020).…”
Section: In-person and Public Self-disclosure Of Sexual Assaultmentioning
confidence: 99%
“…International research shows that rates of nondisclosure among victims of sexual violence range from 19 percent to 48 percent (Ahrens, Rios-Mandel, Isas & del Carmen Lopez, 2010;Carretta et al, 2016;Carson, Babad, Brown, Brumbaugh, Castillo & Nikulina, 2019;Hébert, Tourigny, Cyr, McDuff & Joly, 2009;Jacques-Tiura, Tkatch, Abbey & Wegner, 2010;Ullman, 2011). Feelings of shame, guilt, self-blame, fear of not being believed, fear of negative social reactions, not recognizing the event as a crime and not wanting to involve the police are mentioned as the most important barriers to disclose (Carretta et al, 2016;Sable, Danis, Mauzy & Gallagher, 2006;Starzynski, Ullman, Filipas, & Townsend, 2005;Thompson, Sitterle, Clay & Kingree, 2007;Ullman, O'Callaghan, Shepp & Harris, 2020;Zinzow & Thompson, 2011).…”
Section: Online Disclosure Of Sexual Victimisation: a Systematic Reviewmentioning
confidence: 99%
“…To our knowledge, previous quantitative studies have not assessed whether survivors choose to disclose to certain individuals because of the perceived psychological functioning or attitudes of that individual. However, in a qualitative study, Ullman et al (2020) found that some survivors of sexual assault chose not to disclose owing to concerns about burdening others because they believed that available recipients would lack critical knowledge about how to be supportive, or because they feared possible recipients would hold violence-supportive norms and attitudes.…”
Section: Who Receives Ipv and Sexual Assault Disclosures?mentioning
confidence: 99%
“…For example, future research should assess whether survivors were aware that the disclosure recipient had a history of victimization or were experiencing heightened levels of psychological symptoms (e.g., PTSD or depressive symptoms), and whether these factors influenced their decision to disclose to that individual. Some disclosures may not be offered voluntarily (Ullman et al, 2020); additional research is needed to explore predictors and outcomes of such disclosures and how they might differ from voluntary disclosures. In addition, the context in which individuals receive disclosures must be better understood, including the level of disclosure detail, the relationship between the survivor and the disclosure recipient, the setting in which they are told (e.g., while intoxicated or sober, in front of others or privately), and how disclosures unfold over time.…”
Section: Limitationsmentioning
confidence: 99%